Beidnennung und kognitive Repräsentanz - Stocker, Christa (My University, 2000)
The studies by BRAUN et al. (1998), KLEIN (1988) and KHOSROSHAHI (1989) show that masculine generics (appellatives and pronouns) tend to trigger associations of males rather than of males and females. Even the use of gender splittings and neutral generic pronouns (he or she, she or he, they) respectively does not inevitably lead to an appropriate mental representation of female and male referents. The fact that women often remain mentally underrepresented in gender neutral situations, even though the personal reference is carried out through gender splitting forms, depends on the mechanisms of categorization, on the fact that most situations are gendered, and on a general gendercentrism. Associations made by recipients therefore crucially depend on the following three factors: First on the recipient’s gender, second on whether a situation is dominantly linked to male or female connotations, and third on whether the named category has gendered category-bound features.